An interpretative phenomenological analysis of the sensory experiences of space among children under Autism Spectrum Disorder (ASD) in the Special Education (SPED) center in Tagum City - Buagas, Julie Anne M.; Franco, Sheena Marie R. (2023)
This study aims to explore the sensory experiences of children with autism spectrum disorder (ASD) in the Special Education (SPED) Center in Tagum City using Interpretative Phenomenological Analysis and identify what signifiers in the space stimulated sensory experiences to determine the affordances in the built environment. Fifteen (15) participants with a primary diagnosis of autism spectrum disorder who were currently enrolled in the Magugpo Pilot Imelda Elementary School - SPED Center were purposively selected for this study. Primary data were collected through spatial assessment checklist, direct observation using A-B-C behavior chart, and semi-structured interviews while secondary data, i.e., key informant interview and support from previous studies relating to the responses of children with sensory disabilities and the effects of spatial attributes in sensory experience were utilized to support trustworthiness of the study. After the spatial assessment checklist, researcher identified various zones to be observed during the direct observation process, while semi-structured interview was conducted in the last collection. The data from the spatial assessment, direct observation and semi-interviews had been analyzed in accordance with the data analysis steps specified by Smith et al. (2009) for interpretative phenomenological studies. Five essential themes relating to the sensory experiences of space among children under autism spectrum disorder were identified by the transcripts: ?Visual Structure in Signs?; ?Stairs is to Danger?; ?Giving Options is a Must?; ?Behavior Changes with Environmental Changes?; and ?Engaging in Bright Places?.
Thesis (BS Architecture--University of the Philippines Mindanao, 2023